The Future of Central European Studies. Issue 1 (28th March 2018) - Baranowski, Shelley
Abstract : It is obviously difficult to envision the future of Central European studies with any precision. The broader context that surrounds historians, as well as scholars in other disciplines, influences the topics and methodologies they choose. In recent years (i.e., the post-1990, neoliberal era), transnational, global, and imperialism studies have had a significant impact on the historical profession at large. As David Blackbourn observed in a 2013 address to the German Studies Association, ambitious "deep history" projects that cut across multiple cultures and historical periods have recently thrived, prompting him to encourage historians of Germany to push beyond their narrow graduate training and embrace such undertakings. To be sure, historians of Central Europe have adapted to prevailing trends in the discipline (discussed later), but concerns about the chronological, spacial, methodological, and topical limitations of the field have arisen. Even if scholars of Central Europe utilize different methodologies and approaches, they rarely pioneer. Rather, they latch onto the innovations that other fields have spawned instead of breaking new ground.